Promoting and protecting minority rights: a guide for advocates (United Nations, 2012)
Minorities make significant contributions to the richness and diversity of society, and States that recognize and promote minority rights are more likely to remain tolerant and stable. The United Nations and other intergovernmental organizations recognize that minority rights are essential to protect those who wish to preserve and develop values and practices which they share with other members of their community. This Guide offers information related to norms and mechanisms developed to protect the rights of persons belonging to national, ethnic, religious or linguistic minorities. It provides detailed information about procedures and forums in which minority issues may be raised within the United Nations system and in regional systems. It is hoped that this Guide will be useful in assisting minority advocates to make full and effective use of existing international mechanisms and, ultimately, to promote and protect the rights guaranteed under international instruments.